Rice straw derived cellulose acetate / TiO2 fiber membrane and preparation method and application thereof
Through electrospinning-electrospraying technology, TiO2 nanoparticles are uniformly anchored on the surface of cellulose acetate nanofibers, which solves the problem of internal agglomeration and recycling of nanoparticles, and realizes a highly efficient photocatalytic and environmentally friendly fiber membrane catalyst.
Patent Information
- Application Number
- CN202411618523.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-03-11
AI Technical Summary
In the prior art, TiO2 nanoparticles are mainly located inside the fibers in cellulose acetate fiber membranes, resulting in poor photocatalytic effects and nanoparticles are prone to agglomeration and difficult to recover.
Using electrospinning-electrospraying technology, TiO2 nanoparticles are uniformly anchored on the surface of cellulose acetate nanofibers, and are carried out simultaneously by electrospinning and electrostatic spraying to ensure that the nanoparticles are exposed to the fiber surface.
The photocatalytic activity and chemical stability of the photocatalyst are improved, the exposure and utilization of nanoparticles are enhanced, operating costs are reduced, and environmental pollution is reduced.
Smart Images

Figure CN119593144A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of crop straw resource utilization, and in particular to a rice straw-derived cellulose acetate / TiO2 fiber membrane and a preparation method and application thereof. Background Art
[0002] Solar energy is a renewable and sustainable natural energy source that can be used for photocatalysis. Solar photocatalytic technology has the advantages of low secondary pollution, mild reaction conditions, high efficiency, fast speed, and non-selectivity. Therefore, it can make full use of solar energy to generate renewable clean energy, effectively alleviate the crisis of fossil energy depletion, and at the same time alleviate the atmospheric greenhouse effect. Semiconductor photocatalysts are not only excellent materials for hydrogen production, but also can efficiently remove various organic pollutants. In addition, it can also meet the needs of renewable energy and environmental purification. Semiconductor photocatalytic technology can not only generate clean energy but also degrade chemical pollutants. It is one of the most effective technologies to solve the energy crisis and environmental pollution. At present, common semiconductor photocatalysts include TiO2, g-C3N4, ZnO, BiPO4 and CdS. TiO2 (P25) is one of the most widely studied semiconductor photocatalysts. It has attracted widespread attention due to its low cost, high natural abundance, environmental friendliness, rich crystalline forms, good chemical stability and excellent optical properties. P25 nanoparticles usually have a relatively small particle size and a large specific surface area, so they can promote photocatalytic reactions. However, P25 is easy to aggregate in practical applications, which makes it difficult to recover from the solution and easy to lose, which is not conducive to recycling and application. This will not only increase operating costs, but also may cause secondary pollution to the environment.
[0003] The rapid development of agriculture has increased crop yields, but it has also produced a large amount of crop straw. The comprehensive utilization and efficient management of straw are of great significance to the green and low-carbon transformation of agriculture. At present, the main methods of dealing with excess rice straw are incineration, landfill composting and livestock feed, but the utilization rate of rice straw is not high. The cellulose in rice straw can be used as a raw material for the production of cellulose acetate (CA), which is another way to reduce environmental pollution. By loading P25 nanoparticles on a fiber base to prepare nanofiber materials, not only can the P25 nanoparticles be recycled, but the utilization rate of rice straw can also be improved, reducing environmental pollution. In addition, the nanofiber material can also be used as a photocatalyst in the degradation of chemical pollutants.
[0004] In the prior art, patent 202011180869.0 has disclosed a method for preparing rice straw-derived cellulose acetate. In this patent, the preparation of the loaded fiber membrane generally involves blending cellulose acetate (CA) with titanium dioxide nanoparticles. The particles are mainly located inside the fiber, and only when the amount of titanium dioxide nanoparticles added is very large will the particles be exposed outside the fiber to play a photocatalytic role. The internal particles cannot play a photocatalytic role, which makes the overall photocatalytic effect of the loaded fiber membrane poor. Therefore, this application uses electrospinning-electrospray technology, that is, electrospinning and electrostatic spraying are performed simultaneously to anchor TiO2 on cellulose acetate nanofibers, solve the problems of agglomeration and difficulty in recycling of nanoparticles, and realize the high-value utilization of rice straw resources. Efficiently degrade organic pollutants and pathogenic microorganisms in water, effectively alleviate energy shortages and solve environmental pollution problems. Summary of the invention
[0005] Based on the above, the purpose of the present invention is to provide a rice straw-derived cellulose acetate / TiO2 fiber membrane and a preparation method and application thereof, so as to prepare an environmentally friendly cellulose membrane catalyst with excellent photocatalytic performance, good recycling performance and easy recycling.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] A method for preparing a rice straw-derived cellulose acetate / TiO2 fiber membrane comprises the following steps:
[0008] Mixing dichloromethane and acetic acid uniformly to obtain a mixed solvent, adding rice straw-derived cellulose acetate and polyvinyl pyrrolidone powder into the mixed solvent and stirring to obtain a CA / PVP spinning solution;
[0009] TiO2 powder is mixed with C2H5OH and subjected to ultrasonic treatment to obtain TiO2 electrospray solution;
[0010] EE-CA / PVP / TiO2 fiber membrane was prepared by electrospinning-electrospray technology, using CA / PVP spinning solution and TiO2 electrospray solution for simultaneous electrospinning and electrospinning, respectively, to evenly anchor TiO2 nanoparticles on the fiber surface to obtain EE-CA / PVP / TiO2 fiber membrane;
[0011] The EE-CA / PVP / TiO2 fiber membrane was immersed in deionized water to remove polyvinyl pyrrolidone, and then freeze-dried to obtain a rice straw-derived cellulose acetate / TiO2 fiber membrane.
[0012] As a preferred embodiment of the method for preparing a rice straw-derived cellulose acetate / TiO2 fiber membrane, the mass ratio of the rice straw-derived cellulose acetate and the polyvinyl pyrrolidone powder is (3-5):1; the volume ratio of the dichloromethane and the acetic acid is (1-3):1, and the concentration of the polyvinyl pyrrolidone powder in the mixed solvent is 0.025-0.05 g / mL.
[0013] As a preferred embodiment of the method for preparing a rice straw-derived cellulose acetate / TiO2 fiber membrane, the concentration of the TiO2 powder relative to the mixed solvent is 0.005-0.02 g / mL; in the TiO2 electrospray solution, the concentration of the TiO2 powder relative to the C2H5OH is 0.001-0.01 g / mL.
[0014] As a preferred solution for the preparation of rice straw-derived cellulose acetate / TiO2 fiber membranes, the electrospinning-electrospray technology device comprises an electrospinning machine, an electrostatic sprayer and a rotary drum collection device, wherein the electrospinning machine is placed on one side of the rotary drum collection device, and the electrostatic sprayer is placed on the other side of the rotary drum collection device; when the electrospinning-electrospray technology is performed, the electrospinning machine and the electrostatic sprayer are used simultaneously to perform electrospinning and electrostatic spraying, respectively, and a rotary drum collection device is used for collection, wherein the electrostatic sprayer is not connected to a high-voltage power supply when in use, and the electrospinning-electrospray technology allows the nanoparticles in the electrospray liquid to be evenly dispersed on the fiber surface.
[0015] As a preferred scheme for the preparation method of rice straw-derived cellulose acetate / TiO2 fiber membrane, the electrospinning process parameters include: spinning temperature of 23-27°C, humidity of 45-55%; spinning positive voltage of 8-12kV, spinning negative voltage of -4--6kV; feed rate of 0.3-0.5ul / min; the distance between the spinneret and the drum collecting device is 10-20cm.
[0016] As a preferred embodiment of a method for preparing a rice straw-derived cellulose acetate / TiO2 fiber membrane, the method for preparing the rice straw-derived cellulose acetate comprises:
[0017] The rice straw is washed, dried, crushed and sieved to obtain rice straw powder, the rice straw powder is pretreated with an ethanol solution in a high temperature reactor, and then subjected to an alkali treatment and H2O2 bleaching to obtain rice straw-derived cellulose;
[0018] Acetic anhydride and glacial acetic acid are added to the rice straw-derived cellulose to prepare rice straw-derived cellulose acetate through acetylation reaction.
[0019] As a preferred embodiment of the method for preparing a rice straw-derived cellulose acetate / TiO2 fiber membrane, the rice straw particle size is 50 to 100 meshes;
[0020] During the pretreatment process, the mass concentration of the ethanol solution is 60-70wt%, the heating reaction temperature is 160-240°C, and the reaction time is 2-3h;
[0021] During the alkali treatment and H2O2 bleaching process, 4-6wt% alkali solution is used to stir and react at 85-95°C for 1.5-2.5h. After the reaction is completed, it is filtered, and then 2wt% H2O2 solution is heated and stirred at 65-75°C for 1.5-2.5h to obtain rice straw-derived cellulose.
[0022] 8. The method for preparing rice straw-derived cellulose acetate / TiO2 fiber membrane according to claim 6 is characterized in that, during the acetylation reaction, the mass ratio of the rice straw-derived cellulose to the acetic anhydride is 1:(3-5), and the concentration range of the rice straw-derived cellulose in the glacial acetic acid is 0.05-0.07 g / mL.
[0023] A rice straw-derived cellulose acetate / TiO2 fiber membrane is prepared by any of the above-mentioned preparation methods.
[0024] The invention discloses an application of a rice straw-derived cellulose acetate / TiO2 fiber membrane. The rice straw-derived cellulose acetate / TiO2 fiber membrane is used as a photocatalyst in water pollution treatment and photocatalytic sterilization.
[0025] The beneficial effects of the present invention are:
[0026] The present invention provides a rice straw-derived cellulose acetate / TiO2 fiber membrane and a preparation method and application thereof. The EE-CA / P25 fiber membrane is prepared by electrospinning-electrospray technology. Compared with the E-CA / P25 fiber membrane prepared by the conventional electrospinning method (Electrospinning), the P25 nanoparticles of the EE-CA / P25 fiber membrane are more exposed on the surface of the nanofiber, providing more active sites, and fewer P25 nanoparticles are required to achieve the same photocatalytic effect, thereby improving the separation efficiency of photogenerated carriers and the interfacial charge transfer efficiency, thereby improving the catalytic activity and chemical stability of the material. In addition, the present application uses an electrostatic sprayer for electrostatic spraying, which does not need to be connected to a high-voltage power supply when used, is easy to use, and reduces process costs.
[0027] Under visible light irradiation, EE-CA / P25 (0.05) The fiber membrane has a photocatalytic degradation rate of MB (methylene blue) dye of more than 99.13% in 30 minutes, and a photocatalytic degradation rate of TC (tetracycline) of more than 83.59%. After multiple cycles of use, it still maintains an excellent photocatalytic degradation rate of more than 97.49%, with excellent cycle performance.
[0028] For the study of photocatalytic antibacterial performance, EE-CA / P25 (0.05) When the fiber membrane was irradiated with λ=365nm light for 60min, the antibacterial rate against Escherichia coli was as high as 98.42%, showing good antibacterial performance. (0.05) The fiber membrane has a larger specific surface area, a smaller band gap energy value and a stronger photocatalytic activity, and can be widely used in the fields of degradation of pollutants in water and antibacterial. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments of the present invention. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the contents of the embodiments of the present invention and these drawings without paying any creative work.
[0030] Figure 1 The SEM and HR-TEM images show that (ab)EE-CA / P25 (0.05) SEM images of EE-CA / P25; (cd) (0.03) SEM images of EE-CA / P25; (ef) (0.05) SEM image of EE-CA / P25 (0.10) SEM images of E-CA / P25; (ij) (0.05) SEM images of: (kl) EE-CA / P25 (0.05) HR-TEM image of fiber membrane;
[0031] Figure 2 EE-CA / P25 (0.05) XRD pattern of fiber membrane;
[0032] Figure 3 FT-IR spectra, wherein (a) is the FT-IR spectra of the reaction raw materials; (b) is the FT-IR spectra of the products prepared in Examples 1-3 and Comparative Example 1;
[0033] Figure 4 CA, E-CA / P25 (0.05) and EE-CA / P25 (0.05) N2 adsorption-desorption isotherms and pore size distribution of fiber membranes;
[0034] Figure 5 is the UV-visible diffuse reflectance spectrum and energy band curve diagram, where (a) CA, E-CA / P25 (0.05)UV-visible diffuse reflectance spectra of EE-CA / P25 fiber membranes with different contents; (b) E-CA / P25 (0.05) and EE-CA / P25 (0.05) Energy band diagram of fiber membrane;
[0035] Figure 6 CA, E-CA / P25 (0.05) and EE-CA / P25 (0.05) Thermogravimetric analysis of fiber membrane;
[0036] Figure 7 CA, E-CA / P25 (0.05) and fluorescence spectra of EE-CA / P25 fiber membranes with different contents;
[0037] Figure 8 It curve and EIS spectrum, where (a) EE-CA / P25 (0.05) and E-CA / P25 (0.05) it curve of fiber membrane; (b) EIS spectrum;
[0038] Fig. 9 is the photocatalytic degradation efficiency and the corresponding pseudo-first-order rate constant, where (ab) the photocatalytic degradation efficiency of methylene blue and the corresponding pseudo-first-order rate constant; (cd) EE-CA / P25 (0.05) Degradation efficiency of fiber membranes for different dyes and the corresponding pseudo-first-order rate constants; (ef) EE-CA / P25 (0.05) Degradation efficiency of fiber membranes for different antibiotics and the corresponding pseudo-first-order rate constants;
[0039] Fig.10 EE-CA / P25 (0.05) Repeated test diagram of the fiber membrane's photocatalytic degradation of methylene blue;
[0040] Fig.11 EE-CA / P25 (0.05) Time-varying diagram of the 3D fluorescence spectrum of the fiber membrane, where (ac) methylene blue; (df) rhodamine B; (gi) methyl orange;
[0041] Fig.12 EE-CA / P25 (0.05) Degradation efficiency of methylene blue by fiber membrane under the action of different capture agents (a) and the corresponding pseudo-first-order rate (b);
[0042] Fig.13 The antibacterial effect image, bacterial survival rate curve and bacterial removal efficiency bar graph, where (ad) blank test; (eh) EE-CA / P25 (0.05)Dark's antibacterial effect image; (il)EE-CA / P25 (0.05) Light on antibacterial effect image; (m) bacterial survival rate curve; (n) bacteria removal efficiency bar graph of the sample under visible light (λ=365nm) irradiation. DETAILED DESCRIPTION
[0043] For ease of understanding of the present invention, the present invention will be described more fully below. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive. Unless otherwise defined, all technical and scientific terms used in the present invention belong to the technical field of the present invention.
[0044] This embodiment provides a method for preparing a rice straw-derived cellulose acetate / TiO2 fiber membrane, comprising the following steps:
[0045] S100, mixing dichloromethane and acetic acid uniformly to obtain a mixed solvent, adding rice straw-derived cellulose acetate and polyvinyl pyrrolidone powder into the mixed solvent and stirring to obtain a CA / PVP spinning solution;
[0046] Specifically, the mass ratio of rice straw-derived cellulose acetate and polyvinyl pyrrolidone powder is (3-5):1; the volume ratio of dichloromethane and acetic acid is (1-3):1, and the concentration of polyvinyl pyrrolidone powder in the mixed solvent is 0.025-0.05 g / ml.
[0047] S200, mixing TiO2 powder with C2H5OH, and ultrasonically treating to obtain a TiO2 electrospray solution;
[0048] Specifically, the concentration of TiO2 powder relative to the mixed solvent is 0.005-0.02 g / mL, and the concentration of TiO2 powder relative to C2H5OH is 0.001-0.01 g / mL. For example, 0.8 g of rice straw-derived cellulose acetate, 0.2 g of polyvinyl pyrrolidone powder, and a mixed solution including 2 ml of acetic acid and 4 ml of dichloromethane are used. At this time, 0.03-0.10 g of TiO2 powder is reacted with 15 ml of anhydrous ethanol solution to prepare a TiO2 electrospray solution for electrospray loading, preferably 0.05 g of TiO2 powder is reacted with 15 ml of anhydrous ethanol solution.
[0049] S300, preparing EE-CA / PVP / TiO2 fiber membrane by electrospinning-electrospray technology, using CA / PVP spinning solution and TiO2 electrospray solution to simultaneously perform electrospinning and electrospinning, respectively, to evenly anchor TiO2 nanoparticles on the fiber surface, and obtain EE-CA / PVP / TiO2 fiber membrane;
[0050] Specifically, titanium dioxide particles are loaded on cellulose acetate nanofibers using electrospinning-electrospinning technology. Pure cellulose acetate fibers are electrospun while nanoparticles containing titanium dioxide are electrosprayed. While the fibers are solidified, the titanium dioxide particles are directly exposed on the fiber surface. There are no nanoparticles inside the fibers, exposing more active sites, hindering the recombination of free carriers, and improving the separation efficiency of photogenerated carriers and the interfacial charge transfer efficiency, thereby improving the catalytic activity and chemical stability of the material.
[0051] Specifically, the device of electrostatic spinning-electrospray technology includes an electrostatic spinning machine, an electrostatic sprayer and a rotary drum collection device, the electrostatic spinning machine is placed on one side of the rotary drum collection device, and the electrostatic sprayer is placed on the other side of the rotary drum collection device; when performing electrostatic spinning-electrospray technology, the electrostatic spinning machine and the electrostatic sprayer are used simultaneously to perform electrostatic spinning and electrostatic spraying respectively, and the rotary drum collection device is used for collection. Preferably, the positions of the electrostatic spinning machine, the electrostatic sprayer and the rotary drum collection device can be in a straight line. Of course, in other embodiments, the positions of the electrostatic spinning machine, the electrostatic sprayer and the rotary drum collection device can also be placed at an angle, and the spray generated by the electrostatic sprayer can be loaded onto the fiber filaments collected by the collection device. In addition, an electrostatic sprayer is used for electrostatic spraying. The electrostatic sprayer does not need to be connected to a high-voltage power supply when used, is easy to use, and reduces process costs. In this embodiment, it is preferably a handheld electrosprayer, which is convenient to operate and reduces process costs. Of course, in other embodiments, a fixed electrosprayer can also be used to meet the load.
[0052] More specifically, the process parameters of electrospinning include: spinning temperature of 23-27°C, humidity of 45-55%; spinning positive voltage of 8-12kV, spinning negative voltage of -4--6kV; feed rate of 0.3-0.5ul / min; the distance between the spinneret and the drum collection device is 10-20cm.
[0053] S400, soaking the EE-CA / PVP / P25 fiber membrane in deionized water to remove polyvinyl pyrrolidone, and freeze-drying to obtain a rice straw-derived cellulose acetate / TiO2 fiber membrane, which is recorded as EE-CA / P25 fiber membrane.
[0054] Specifically, the preparation method of rice straw-derived cellulose acetate includes:
[0055] S001, washing, drying, crushing and sieving the rice straw to obtain rice straw powder, pre-treating the rice straw powder with an ethanol solution in a high-temperature reactor, and then performing an alkali treatment and H2O2 bleaching to obtain rice straw-derived cellulose;
[0056] The rice straw particle size is 50-100 mesh;
[0057] During the pretreatment process, the mass concentration of the ethanol solution is 60-70wt%, the heating reaction temperature is 160-240°C, and the reaction time is 2-3h;
[0058] During the alkali treatment and H2O2 bleaching process, 4-6wt% alkali solution is used to stir and react at 85-95°C for 1.5-2.5h. After the reaction is completed, it is filtered and then heated and stirred with 2wt% H2O2 solution at 65-75°C for 1.5-2.5h to obtain rice straw-derived cellulose.
[0059] S002, adding acetic anhydride and glacial acetic acid to rice straw-derived cellulose to prepare rice straw-derived cellulose acetate through acetylation reaction;
[0060] The mass ratio of rice straw derived cellulose to acetic anhydride is 1:(3-5), the concentration range of rice straw derived cellulose in glacial acetic acid is 0.05-0.07 g / mL, and in a specific embodiment, 7-9 mL of glacial acetic acid is added to every 0.5 g of rice straw cellulose for reaction.
[0061] The present invention will be further described below by means of specific examples.
[0062] Example 1
[0063] The rice straw is washed, dried, crushed and sieved to obtain rice straw powder, and the rice straw powder is pretreated with an ethanol solution in a high-temperature reactor at 200° C. for 3 h, and then subjected to alkali treatment and H2O2 bleaching to obtain rice straw-derived cellulose; 2 g of acetic anhydride and 8 ml of glacial acetic acid are added to 0.5 g of rice straw-derived cellulose to obtain rice straw-derived cellulose acetate through an acetylation reaction; of course, in other embodiments, 1.5 g of acetic anhydride and 7 ml of glacial acetic acid are added to 0.5 g of rice straw-derived cellulose, or 2.5 g of acetic anhydride and 9 ml of glacial acetic acid are added to 0.5 g of rice straw-derived cellulose to obtain rice straw-derived cellulose acetate through an acetylation reaction, which is determined according to actual conditions.
[0064] 4 ml of dichloromethane and 2 ml of acetic acid were evenly mixed to obtain a mixed solvent, 0.8 g of rice straw-derived cellulose acetate and 0.2 g of polyvinyl pyrrolidone powder were added to the mixed solvent, and stirred for 6 hours using a magnetic stirrer to obtain a CA / PVP spinning solution; at this time, the mass ratio of rice straw-derived cellulose acetate and polyvinyl pyrrolidone powder was 4:1; the volume ratio of dichloromethane and acetic acid was 2:1, and the concentration of polyvinyl pyrrolidone powder in the mixed solvent was 0.033 g / mL. Of course, in other embodiments, the mass ratio of rice straw-derived cellulose acetate and polyvinyl pyrrolidone powder was 3:1 or 5:1; the volume ratio of dichloromethane and acetic acid was 3:1 or 1:1, and the concentration of polyvinyl pyrrolidone powder in the mixed solvent was 0.025 g / mL or 0.05 g / mL, which was determined according to actual conditions.
[0065] 0.05 g TiO2 powder was mixed with 15 mL C2H5OH and ultrasonicated for 60 min to obtain TiO2 electrospray solution;
[0066] The electrospinning machine is placed on one side of the drum collecting device, and the electrostatic sprayer is placed on the other side of the drum collecting device. Electrospinning and electrostatic spraying are performed simultaneously. The CA / PVP spinning solution is transferred to a syringe to prepare for electrospinning. When the electrospinning machine starts working, the CA / PVP nanofibers are collected by the drum collecting device, and a handheld electrosprayer filled with TiO2 electrospray solution is used to work at the same time, spraying for 6-8 seconds at a certain interval until the spinning is completed to obtain the EE-CA / PVP / P25 fiber membrane. Among them, the electrospinning process parameters are as follows: the spinning temperature and humidity are 25°C and 50% respectively; the spinning positive and negative voltages are 10kV and -5kV respectively; the feed rate is 0.4ul / min; the distance between the spinneret and the drum collecting device is 15cm.
[0067] The EE-CA / PVP / P25 fiber membrane was soaked in deionized water for 24 h to remove the polyvinyl pyrrolidone and freeze-dried to obtain the rice straw-derived cellulose acetate / TiO2 fiber membrane, which was denoted as EE-CA / P25. (0.05) Fiber membrane.
[0068] Example 2
[0069] The preparation process was basically the same as that of Example 1, wherein 0.1 g TiO2 powder was mixed with 15 mL C2H5OH to obtain a rice straw-derived cellulose acetate / TiO2 fiber membrane, denoted as EE-CA / P25. (0.10) Fiber membrane.
[0070] Example 3
[0071] The preparation process was basically the same as that of Example 1, wherein 0.03 g TiO2 powder was mixed with 15 mL C2H5OH to obtain a rice straw-derived cellulose acetate / TiO2 fiber membrane, denoted as EE-CA / P25. (0.03) Fiber membrane.
[0072] In order to further illustrate the key points of this patent, a comparative case is added for illustration.
[0073] Comparative Example 1
[0074] The same CA / PVP spinning solution as in Example 1 was prepared, and 0.05 g of P25 powder was added to the vigorously stirred CA / PVP spinning solution to obtain a CA / PVP / P25 spinning solution;
[0075] Then the CA / PVP / P25 spinning solution was placed in a syringe equipped with a steel needle for electrospinning. The parameters of the spinning process were: spinning temperature 25 °C, humidity 50%, spinning positive voltage 20 kV, negative voltage -10 kV, feed rate 1.50 ul / min, and the collection distance between the nozzle and the collection device was 15 cm;
[0076] Finally, E-CA / PVP / P25 was prepared by the above electrospinning technology. (0.05) The fiber membrane was immersed in deionized water to remove PVP and freeze-dried to obtain E-CA / P25 (0.05) Fiber membrane.
[0077] Comparative Example 2
[0078] The same rice straw-derived acetate fiber (CA) as in Example 1 was prepared, and CA was directly electrospun to obtain a pure CA fiber membrane.
[0079] The photocatalytic performance of the fiber membranes prepared in Examples 1-3 and Comparative Examples 1-2 was analyzed and relevant photocatalytic tests were performed.
[0080] 1. Photocatalytic performance test
[0081] (1) Photocatalytic degradation test
[0082] Different organic dyes, rhodamine B (RhB), methylene blue (MB) and methyl orange (MO) were used as simulated organic pollutants to evaluate the photocatalytic activity of EE-CA / P25 fiber membrane under visible light irradiation, and all tests were repeated 3 times. First, 50 mg of membrane photocatalyst was added to 50 mL of organic dye aqueous solution (10 mg / L). The above photocatalyst suspension was stirred in the dark for 30 minutes under magnetic stirring. After reaching adsorption-desorption equilibrium, xenon lamp irradiation was used as simulated sunlight irradiation, and the circulating condensed water was set to 20 ° C. 5 mL of equal amount was sampled every 5 minutes, and the resulting solution was filtered through a 0.22 μm filter membrane. The concentrations of RhB, MB and MO solutions were measured at 554 nm, 664 nm and 465 nm respectively using a UV-visible spectrophotometer.
[0083] (2) Photocatalytic cycle test
[0084] In order to verify the stability of the EE-CA / P25 fiber membrane, the membrane catalyst was subjected to 5 cycles of testing under the same photocatalytic conditions as mentioned above: after the photocatalytic test, the EE-CA / P25 fiber membrane was collected and repeatedly washed with anhydrous ethanol and deionized water to make the catalyst surface colorless, and then dried and then subjected to cycle testing. This process was repeated 5 times.
[0085] (3) Photocatalytic antibacterial test
[0086] The photocatalytic antibacterial activity of EE-CA / P25 fiber membrane against Escherichia coli was detected by plate colony counting method. All tests were carried out in parallel 3 times. The nutrient source of bacteria was LB (1g beef extract, 1g NaCl, 2g peptone, 4g agar powder, 200mL H2O). All glassware was sterilized at 121℃ for 30min before testing. The photocatalytic antibacterial test process is described as follows: First, 50mg of EE-CA / P25 (0.05) The fiber membrane is placed in a beaker and diluted with 0.9% NaCl solution. Secondly, the bacteria are taken out of the culture solution and added to the beaker containing the sample so that the bacteria and the sample are fully mixed and in contact in a dark environment. Third, a xenon lamp (λ=365nm) is used as a light source for vertical downward irradiation, and constant stirring is maintained throughout the test. At fixed time intervals, 1mL of the mixture is transferred with a pipette and diluted to an appropriate concentration. Finally, 0.1ml of the bacterial solution is evenly applied to the culture medium using the plate coating method. It is then placed in a constant temperature incubator and cultured overnight at 37°C. The number of colonies on each plate is counted using a colony counter to calculate the photocatalytic inhibition rate of the sample.
[0087] 2. Related characterization and performance analysis
[0088] (1) Morphology and structure characterization
[0089] The surface morphology and element distribution of the materials were observed using a JSM-7100F field emission scanning electron microscope, and the microstructure of the materials was characterized on a JEOL JEM 2100F high-resolution transmission electron microscope.
[0090] like Figure 1 As shown in (ab), the prepared EE-CA / P25 fiber membrane is white, flexible, and a multilayer structure is observed. In order to further study the structural changes of the film, the surface morphology of the nanofiber composite material was characterized by scanning electron microscopy and electron microscopy. Figure 1 As shown in (ch), with the increase of P25 loading, more P25 nanoparticles are anchored on the surface of CA fiber membrane. When the P25 loading is 0.03g, there are few P25 particles on the surface of CA nanofiber. When the amount of P25 added is increased to 0.05g, it can be obviously observed that more P25 nanoparticles are evenly fixed on the surface of nanofiber. When the amount of P25 is increased to 0.10g, it is found that P25 nanoparticles have a large aggregation on the fiber surface. The aggregation phenomenon is caused by the increase in the concentration of P25 in the fixed C2H5OH, which is not conducive to photocatalytic degradation.
[0091] from Figure 1 It can be clearly seen that although the amount of P25 is the same, EE-CA / P25 (0.05)Fiber membrane and E-CA / P25 (0.05) There are significant differences in the morphology of the fiber membranes. Figure 1 EE-CA / P25 in (ef) (0.05) P25 nanoparticles were anchored on the surface of the fiber membrane, which was prepared by electrospinning-electrospray method. Figure 1
[0092] (ij) E-CA / P25 prepared by electrospinning (0.05) Fiber membrane, most of the P25 nanoparticles are wrapped in the fibers, and only a few P25 nanoparticles are exposed. From the perspective of obtaining more exposed P25 nanoparticles, the electrospinning-electrospray method has a more significant advantage than the electrospinning method. The exposure of P25 nanoparticles on the surface of nanofibers provides more active sites, which is beneficial to improve the photocatalytic performance. In addition, Figure 1
[0093] (kl) shows that from EE-CA / P25 (0.05) It can be clearly seen in the TEM image of the fiber membrane that the P25 nanoparticles are uniformly fixed on the surface of the one-dimensional fiber. In addition, clear lattice fringes with a lattice spacing of d = 0.35nm are detected, which corresponds to the (101) crystalline surface of P25. According to the above analysis, both SEM and TEM images show that the P25 nanoparticles are anchored on the surface of the fiber membrane.
[0094] (2) X-ray diffraction (XRD) characterization
[0095] The XRD spectrum of the material was measured using the XRD-7000 X-ray diffractometer of Shanghai Shimadzu Company, and the crystal structure of the material was analyzed by comparing with the standard card. The test conditions were set as follows: the X-ray target source was Cu-Kα, the operating voltage was 40.0 kV, the scanning range was from 5° to 80°, and the scanning speed was 5° / min.
[0096] EE-CA / P25 (0.05) The X-ray diffraction pattern of the fiber membrane is shown in Figure 2 As shown. It can be seen that the prepared EE-CA / P25 (0.05) The fiber film has characteristic diffraction peaks of TiO2. More specifically, there are five characteristic peaks at 25.2°, 38.0°, 48.2°, 54.2° and 55.1°. By comparing (JCPD.No:21-1272), it can be seen that this corresponds to the (101), (004), (200), (105) and (211) crystal planes of anatase TiO2. Figure 2 EE-CA / P25 (0.05) All the diffraction peaks of EE-CA / P25 are pointed to the anatase TiO2 crystal structure. (0.05)The fiber membrane contains P25.
[0097] (3) Fourier transform infrared spectroscopy (FT-IR) characterization
[0098] The surface functional groups of the materials were determined by KBr pellet method on a Thermo Nicolet Avatar 360 Fourier transform infrared spectrometer. The ratio of sample to KBr was about 1:200 and the scanning range was 4000-500 cm -1 .
[0099] The functional group composition of the material was analyzed by Fourier transform infrared spectroscopy. Figure 3 The main characteristic peaks are attributed to CA and TiO2, respectively. Specifically, 1234, 1375, 1751, and 3370 cm -1 The peaks at 1422 and 1650 cm-1 are attributed to the CO stretching vibration of the CA film, the CH bond stretching vibration in the -O(C=O)-CH3 group, the stretching vibration of C=O, and the -OH stretching vibration. -1 The characteristic peaks at 470-700cm are the absorption peaks of -CH2- bending vibration and C=O vibration transition of PVP molecules. -1 The more obvious broad absorption peak in the range is caused by the stretching movement of Ti-O-Ti bonds in TiO2. Figure 3 As shown in (b), all the prepared samples have a wavelength range of 1200-1751 cm -1 Multiple peaks at 3370 cm -1 The peaks at 1047 cm-1 correspond to the CO stretching vibration, C=O stretching vibration in the CA molecule and the OH stretching vibration of the HOH bond bending vibration in the water molecule adsorbed on the TiO2 surface. -1 The peak at 470-700cm is the vibration of the COC pyran ring skeleton of CA. -1 The broad absorption peak in the range is considered to be the characteristic absorption peak of TiO2. PVP is at 1422cm -1 and 1650cm -1 The intensity of the characteristic peaks near the CA fiber membrane was significantly weakened. It can be seen that most of the PVP in the fiber membrane has been dissolved after the water treatment. All the prepared samples showed the same infrared characteristic peaks as CA and TiO2, which shows that the TiO2 nanoparticles were successfully introduced into the CA fiber membrane by synchronous electrospraying.
[0100] (4) Characterization of specific surface area and pore size distribution
[0101] The nitrogen adsorption-desorption test of the material was carried out using the American MicroActiveASAP 2460 specific surface area analyzer to detect the specific surface area, pore volume and pore size distribution of the material. N2 was used as the protective gas during the degassing treatment and the temperature was set to 90°C.
[0102] Morphological characteristics play a crucial role in the successful preparation of photocatalysts. Figure 4 As shown, CA, EE-CA / P25 were analyzed by N2 adsorption-desorption isotherms and pore size distribution. (0.05) and E-CA / P25 (0.05) Structural characteristics of photocatalysts. At the same time, the differences in specific surface area of nanofibers prepared by different spinning processes were also analyzed. According to the Brunauer-Emmett-Teller classification, all three photocatalysts showed type IV adsorption isotherms. Their average pore sizes were between 2-50nm, and they all had obvious hysteresis loops, which are typical characteristics of the adsorption and desorption curves of mesoporous materials. The results show that these materials all have mesoporous structures. As shown in Table 1, EE-CA / P25 prepared by electrospinning-electrospray (0.05) The specific surface area of the fiber membrane is 20.13m 2 ·g -1 , is CA fiber membrane (16.11m 2 ·g -1 ). However, the E-CA / P25 prepared by electrospinning (0.05) The specific surface area is 12.39m 2 ·g -1 , which is lower than that of CA fiber membrane. This may be due to the aggregation of P25 nanoparticles inside the fiber during electrospinning, while the electrospinning-electrospray method can ensure that P25 nanoparticles are evenly fixed on the surface of CA nanofibers, which makes EE-CA / P25 (0.05) The fiber membrane has a larger specific surface area. Although the increase in specific surface area is not much compared with the pure CA membrane, it can increase the active sites and thus improve the EE-CA / P25 (0.05) photocatalytic performance.
[0103] Table 1 Specific surface area and pore structure parameters of materials
[0104]
[0105] (5) UV-Visible absorption spectroscopy (DRS) characterization
[0106] The TU-1810 spectrophotometer was used for analysis, and the measured UV-visible diffuse reflectance spectra were converted into absorption spectra using the Kubelka-Munk formula.
[0107] The optical properties of photocatalysts such as Figure 5As shown in the figure, it can be seen that the pure CA fiber membrane shows a strong absorption band edge at 375nm. (0.05) The absorption band edge is from 380nm (E-CA / P25 (0.05) ) red shifted to 406nm (EE-CA / P25 (0.05) ), which indicates that the band gap of the film material is relatively large relative to E-CA / P25 (0.05) The band gap energy of the material can be calculated by the Kubelka-Munk function
[0108] (αhv) n =A(hv-Eg)
[0109] Where: α represents the absorption coefficient, hν is the photon energy, A is a constant, Eg is the band gap energy value, and n is 2. 2 Plot hν, such as Figure 5 (b) EE-CA / P25 (0.05) and E-CA / P25 (0.05) The band gaps are 3.05eV and 3.26eV respectively.
[0110] (6) Thermogravimetric (TG) characterization
[0111] The TG test was carried out using a Hitachi STA 7300 thermogravimetric analyzer at a heating rate of 10 °C / min in an air flow from room temperature to 800 °C.
[0112] CA, EE-CA / P25 (0.05) and E-CA / P25 (0.05) TG analysis of fiber membrane Figure 6 As shown. It can be seen that the TG curve trends and shapes of the fiber membranes prepared by different spinning processes are roughly the same. Specifically, the weight loss from room temperature to 120°C is caused by the loss of water adsorbed on the sample surface, while 120°C to 300°C is the pre-thermolysis transition stage. In this stage, the curve drops more gently and the loss rate of the sample is also small. However, CA, EE-CA / P25 (0.05) and E-CA / P25 (0.05) The weight loss phenomenon occurred in the temperature range of 300-500℃. Cellulose is unstable at high temperature, so it will partially decompose and produce carbonized substances at high temperature. After the temperature rises to 500℃, the curve tends to be flat, and the sample weight tends to be fixed. The final fixed value is the P25 content in the fiber membrane. By comparing with the residual amount of CA fiber membrane, EE-CA / P25 is calculated. (0.05) and E-CA / P25 (0.05) The P25 contents in the fiber membranes were 5.49% and 9.51%, respectively.
[0113] (7) Three-dimensional fluorescence (3DEEM) characterization
[0114] The three-dimensional fluorescence spectra (3DEEM) were recorded using a Fluoromax-4 fluorescence spectrometer, with the excitation wavelength (Ex) and emission wavelength (Em) both ranging from 250 to 700 nm.
[0115] The fluorescence spectra of CA membrane, EE-CA / P25 and E-CA / P25 fiber membranes are shown in Figure 7 As shown in Figure 2, the intensity of the fluorescence spectrophotometer (PL) PL emission spectrum is weak, reflecting the low binding rate of photogenerated electron-hole pairs. Figure 7 It can be seen that the photoluminescence emission peak of CA film is the strongest near 422nm. However, the fluorescence intensity of CA / P25 fiber membrane becomes lower after loading P25 nanoparticles, indicating that its separation efficiency of photogenerated carriers is improved. When more P25 nanoparticles are anchored on the surface of CA / P25 fiber membrane, the fluorescence intensity first weakens and then increases. EE-CA / P25 (0.05) The fluorescence intensity of E-CA / P25 was the weakest, which was because the P25 nanoparticles exposed on the surface of nanofibers were evenly distributed. (0.05) The fluorescence intensity of the fiber membrane is EE-CA / P25 (0.05) The fluorescence intensity of the fiber film is strong, which is related to the electrospinning method. Therefore, most of the P25 nanoparticles are wrapped in the fiber. (0.05) Only a few P25 nanoparticles are exposed in the fiber membrane. In summary, it can be preliminarily inferred that EE-CA / P25 with the lowest peak light concentration (0.05) The fiber membrane has a relatively high photocatalytic ability.
[0116] 3. Other performance analysis
[0117] (1) Photoelectrochemical performance test
[0118] Photoelectrochemical tests confirmed the effectiveness of photogenerated charge separation and transfer. Figure 8 (a) describes EE-CA / P25 (0.05) and E-CA / P25 (0.05) Photocurrent curve under visible light irradiation. Figure 8 As can be seen from (a), EE-CA / P25 (0.05) The transient photocurrent response is higher than that of E-CA / P25 (0.05) Since the photocurrent response is related to the diffusion rate of photogenerated electrons, a stronger photocurrent response means faster photogenerated charge transfer. In addition, EIS tests were also used to determine the interfacial charge migration. The results are shown in Figure 2. Figure 8 As shown in (b), it is obvious that EE-CA / P25 (0.05)The EIS semicircle radius is smaller than E-CA / P25 (0.05) , which means EE-CA / P25 (0.05) The above photoelectrochemical test results confirm that EE-CA / P25 (0.05) Compared to E-CA / P25 (0.05) It has better photogenerated charge separation and transfer performance.
[0119] (2) Photocatalytic performance
[0120] The adsorption and oxidation activities of different photocatalysts were studied by photocatalytic degradation of organic dyes and antibiotics. Fig. 9 All the prepared samples were tested for the photocatalytic degradation of methyl bromide as shown in the figure. In addition, blank control tests were performed on MB dye and CA membrane under the same conditions, and EE-CA / P25 was tested under dark conditions. (0.05) The membrane was subjected to adsorption test as a control test. After 30 min of illumination, the highest degradation efficiency of the prepared CA / P25 fiber membrane for MB dye was 99.40%. Fig. 9 As can be seen from the curve in (a), with the increase of P25 loading, the degradation of EE-CA / P25 fiber film photocatalyst first increases and then decreases. This result shows that anchoring an appropriate amount of P25 nanoparticles on the surface of CA nanofibers can effectively improve the photocatalytic activity. Under the same photocatalytic conditions, Fig. 9 (b) EE-CA / P25 (0.05) The photocatalytic activity was the best, and the reaction rate reached 0.1328min -1 , respectively CA membrane, EE-CA / P25 (0.03) EE-CA / P25 (0.10) and E-CA / P25 (0.05) Therefore, when MB was used as the research object for photocatalytic testing, EE-CA / P25 prepared by electrospinning-electrospray (0.05) The photocatalytic performance of the fiber membrane is better than that of E-CA / P25 prepared by electrospinning (0.05) It is further speculated that anchoring P25 nanoparticles on the surface of CA nanofibers may promote the separation and transfer of electrons, which helps to improve the performance of photocatalytic degradation of MB.
[0121] EE-CA / P25 (0.05) The degradation efficiency and corresponding pseudo-first-order rate constants of different dyes RhB, MB and MO are shown in Figure 2. Fig. 9 (cd) At 30 min, EE-CA / P25 (0.05)The photocatalytic degradation efficiencies of MB, RhB and MO were 99.40%, 58.16% and 21.59%, respectively. (0.05) The photocatalytic degradation effect on MB was the best, followed by RhB and MO. Fig. 9 (ef) shows, EE-CA / P25 (0.05) It also has photocatalytic degradation effect on three different antibiotics: TC, CIP and SMX. Among them, the photocatalytic degradation effect of TC is the strongest. The photocatalytic degradation efficiency of TC reaches 83.59% after 30 minutes of illumination. (0.05) The fiber membrane has excellent photocatalytic degradation and water treatment properties.
[0122] In addition, the reusability of the fiber film photocatalyst was evaluated. (0.05) The fiber membrane was subjected to five cycles of photocatalytic degradation of MB dye. After each photocatalytic degradation test, EE-CA / P25 was taken out. (0.05) The fiber membrane was washed several times with C2H5OH and deionized water and then dried in an oven at 80 °C for the next photocatalytic degradation cycle test. Fig.10 EE-CA / P25 (0.05) Cyclic photocatalytic degradation performance of MB dye. The photocatalyst maintained an excellent photocatalytic degradation efficiency of 97.49% after 5 cycles. This shows that EE-CA / P25 (0.05) It not only has a unique flexible membrane structure and is easy to reuse, but also exhibits excellent photocatalytic stability.
[0123] (3) Three-dimensional fluorescence spectroscopy
[0124] Analysis of EE-CA / P25 (0.05) After studying the photocatalytic degradation performance of the fiber membrane towards different organic dyes, the degradation process was further studied using three-dimensional fluorescence spectroscopy. Fig.11 As shown in (a), the two three-dimensional fingerprint peaks of MB at 500-700nm and 250-300nm before the photocatalytic reaction. After the dark reaction reached adsorption equilibrium for 30 minutes, the intensity of the two three-dimensional fingerprint peaks weakened. After the photocatalytic reaction was carried out for 30 minutes, Fig.11 As shown in (c), the 3D fingerprint peak almost completely disappeared, and MB was basically completely degraded. Fig.11 As shown in (di), when RhB and MO organic dyes were used for simulated pollution, the spectral signals and colors of RhB and MO dyes only changed slightly. Therefore, the changes in the three-dimensional fingerprint peaks before and after degradation indicate that EE-CA / P25 (0.05)The fiber membrane had weak degradation performance for RhB and MO dyes within 30 min, but had good photocatalytic degradation efficiency for MB dye.
[0125] (4) Photocatalytic mechanism
[0126] In order to study the (0.05) In order to determine which active species plays a major role in the photocatalytic degradation of MB by fiber membrane, p-benzoquinone (BQ), triethanolamine (TEOA) and isopropyl alcohol (IPA) were added to the photocatalytic system. Among them, BQ captures superoxide radicals (·O2 - ), TEOA captures photogenerated holes (h + ), IPA captures hydroxyl radicals (·OH)
[168] .like Fig.12 As shown in Figure 2, all degradation characteristics conform to pseudo-first-order kinetics. After adding BQ and IPA to the photocatalytic degradation system, EE-CA / P25 (0.05) The photocatalytic degradation efficiency of the fiber membrane decreased to 60.45% and 81.35%, respectively. (0.05) The degradation performance of NH4CO3 dropped sharply, and the degradation efficiency dropped from 99.99% to 50.95%. Fig.12 The rate constant in (b) can be determined as h + It is the main active species in the degradation process, and the secondary active species is O2 - The order of action of active species in the photocatalytic degradation process is h + > O2 - >·OH.
[0127] (5) Photocatalytic antibacterial
[0128] In order to accurately assess EE-CA / P25 (0.05) The antibacterial properties of the fiber membrane were calculated by calculating the final bacterial colony counts of the test plate and the control plate grown overnight in an aerobic environment at 37°C. Fig.13 As shown in (ad), in the blank test under λ=365nm light irradiation, the number of colonies after illumination was almost unchanged, which indicates that 365nm visible light has a weak killing effect on Escherichia coli. Fig.13 (mn) further confirmed that almost all bacteria were alive after 60 minutes of illumination, with a bacterial survival rate of up to 95.18%. This proves that the killing effect of light source alone on E. coli is minimal. (0.05) Comparative antibacterial test of fiber membrane under non-light conditions, such as Fig.13 As shown in (eh), it can be observed that the number of E. coli colonies after 60 minutes is not much different. Therefore, EE-CA / P25 (0.05)The possibility that the fiber membrane has antibacterial activity under dark conditions. Fig.13 (j) EE-CA / P25 (0.05) After 20 minutes of light exposure, the number of E. coli colonies on the fiber membrane decreased significantly, and the colony survival rate dropped sharply to 43.18%. Fig.13 As shown in (kl), a small number of bacterial colonies can be seen after 40 minutes of illumination, and almost all bacteria are killed after 60 minutes of illumination, with an antibacterial efficiency of 98.42%, which indicates that EE-CA / P25 (0.05) The fiber membrane has good antibacterial properties under light.
[0129] In summary:
[0130] Compared with the E-CA / P25 fiber membrane prepared by the traditional electrospinning method, the P25 nanoparticles of the EE-CA / P25 fiber membrane prepared by the electrospinning-electrospinning method are more exposed on the surface of the nanofibers, providing more active sites, which is beneficial to improving the photocatalytic performance.
[0131] Especially EE-CA / P25 (0.05) The fiber membrane has a larger specific surface area, a smaller band gap energy value and a stronger photocatalytic activity. Under visible light irradiation, EE-CA / P25 (0.05) The fiber membrane has a photocatalytic degradation rate of up to 99.13% for MB (methylene blue) dye in 30 minutes, and a photocatalytic degradation rate of 83.59% for TC (tetracycline). After five cycles of use, it still maintains an excellent photocatalytic degradation rate of 97.49%, which can be used in the industrial field to degrade organic pollutants. (0.05) When the fiber membrane was irradiated with visible light (λ=365nm) for 60 minutes, the antibacterial rate against Escherichia coli was as high as 98.42%, showing good antibacterial performance.
[0132] The above are only preferred embodiments of the present invention and the technical principles used. Those skilled in the art will understand that the present invention is not limited to the specific embodiments described herein, and that various obvious changes, readjustments and substitutions can be made by those skilled in the art without departing from the scope of protection of the present invention. Therefore, although the present invention is described in more detail through the above embodiments, the present invention is not limited to the above embodiments, and may include more other equivalent embodiments without departing from the concept of the present invention, and the scope of the present invention is determined by the scope of the appended claims.
Claims
1. A method for preparing a rice straw-derived cellulose acetate / TiO2 fiber membrane, characterized in that: The following steps are involved: Mixing dichloromethane and acetic acid uniformly to obtain a mixed solvent, adding rice straw-derived cellulose acetate and polyvinyl pyrrolidone powder into the mixed solvent and stirring to obtain a CA / PVP spinning solution; TiO2 powder is mixed with C2H5OH and subjected to ultrasonic treatment to obtain TiO2 electrospray solution; EE-CA / PVP / TiO2 fiber membrane was prepared by electrospinning-electrospray technology, using CA / PVP spinning solution and TiO2 electrospray solution for simultaneous electrospinning and electrospinning, respectively, to evenly anchor TiO2 nanoparticles on the fiber surface to obtain EE-CA / PVP / TiO2 fiber membrane; The EE-CA / PVP / TiO2 fiber membrane was immersed in deionized water to remove polyvinyl pyrrolidone, and then freeze-dried to obtain a rice straw-derived cellulose acetate / TiO2 fiber membrane.
2. The method for preparing the rice straw-derived cellulose acetate / TiO2 fiber membrane according to claim 1, characterized in that: The mass ratio of the rice straw-derived cellulose acetate to the polyvinyl pyrrolidone powder is (3-5):1; the volume ratio of the dichloromethane to the acetic acid is (1-3):1, and the concentration of the polyvinyl pyrrolidone powder in the mixed solvent is 0.025-0.05 g / mL 。 3. The method for preparing the rice straw-derived cellulose acetate / TiO2 fiber membrane according to claim 2, characterized in that: The concentration of the TiO2 powder relative to the mixed solvent is 0.005-0.02 g / mL; in the TiO2 electrospray solution, the concentration of the TiO2 powder relative to the C2H5OH is 0.001-0.01 g / mL.
4. The method for preparing the rice straw-derived cellulose acetate / TiO2 fiber membrane according to claim 1, characterized in that: The electrospinning-electrospraying technology device comprises an electrospinning machine, an electrostatic sprayer and a rotary drum collecting device, wherein the electrospinning machine is placed on one side of the rotary drum collecting device, and the electrostatic sprayer is placed on the other side of the rotary drum collecting device; When the electrospinning-electrospraying technology is used, an electrospinning machine and an electrostatic sprayer are used simultaneously to perform electrospinning and electrostatic spraying respectively, and a rotary drum collection device is used for collection. The electrostatic sprayer is not connected to a high-voltage power supply when in use. The electrospinning-electrospraying technology allows the nanoparticles in the electrospray liquid to be evenly dispersed on the fiber surface.
5. The method for preparing the rice straw-derived cellulose acetate / TiO2 fiber membrane according to claim 4, characterized in that: The electrospinning process parameters include: spinning temperature of 23-27°C, humidity of 45-55%, spinning positive voltage of 8-12kV, spinning negative voltage of -4--6kV, feeding speed of 0.3-0.5ul / min, and the distance between the spinneret and the drum collecting device of 10-20cm.
6. The method for preparing the rice straw-derived cellulose acetate / TiO2 fiber membrane according to claim 1, characterized in that: The preparation method of the rice straw-derived cellulose acetate comprises: The rice straw is washed, dried, crushed and sieved to obtain rice straw powder, the rice straw powder is pretreated with an ethanol solution in a high temperature reactor, and then subjected to an alkali treatment and H2O2 bleaching to obtain rice straw-derived cellulose; Acetic anhydride and glacial acetic acid are added to the rice straw-derived cellulose to prepare rice straw-derived cellulose acetate through acetylation reaction.
7. The method for preparing the rice straw-derived cellulose acetate / TiO2 fiber membrane according to claim 6, characterized in that: The rice straw particle size is 50 to 100 meshes; During the pretreatment process, the mass concentration of the ethanol solution is 60-70wt%, the heating reaction temperature is 160-240°C, and the reaction time is 2-3h; During the alkali treatment and H2O2 bleaching process, 4-6wt% alkali solution is used to stir and react at 85-95°C for 1.5-2.5h. After the reaction is completed, it is filtered, and then 2wt% H2O2 solution is heated and stirred at 65-75°C for 1.5-2.5h to obtain rice straw-derived cellulose.
8. The method for preparing the rice straw-derived cellulose acetate / TiO2 fiber membrane according to claim 6, characterized in that: During the acetylation reaction, the mass ratio of the rice straw-derived cellulose to the acetic anhydride is 1:(3-5), and the concentration range of the rice straw-derived cellulose in the glacial acetic acid is 0.05-0.07 g / mL.
9. A rice straw derived cellulose acetate / TiO2 fiber membrane, characterized in that: Prepared by the preparation method according to any one of claims 1 to 8.
10. An application of the rice straw derived cellulose acetate / TiO2 fiber membrane according to claim 9, characterized in that: The rice straw-derived cellulose acetate / TiO2 fiber membrane is used as a photocatalyst in water pollution treatment and photocatalytic sterilization.
Citation Information
Patent Citations
Antibacterial air filter felt, and preparation method and application thereof
CN103446803A
Cellulose acetate / titanium dioxide composite nanofiber adsorption film and preparation method thereof
CN103898676A
Preparing method for nanoparticle / fiber composite membrane
CN105251376A
Device for preparing functional nanofiber
CN105734697A
Microorganism-loaded sandwiched micro-nano fiber composite membrane and preparation method and application thereof
CN106282153A